The role of dentistry in the diagnosis of cleidocranial dysplasia: report of two cases - Leite, Pryscilla Batista; Carvalho, Caroline Cavaignac Silva; Heimlich, Fernanda Vieira; Freire, Nathalia Almeida; Ramos, Maria Eliza Barbosa; Israel, Monica Simoes (Journal of Oral Diagnosis, 2020)
Cleidocranial Dysplasia presents as a rare condition arising from a change in the RUNX2 gene. This alteration presents both skeletal and dental characteristics that preferentially affect the clavicles, ribs, pelvis and gnathic bones. Supernumerary teeth are one of the dental findings of CCD and hypermobility of the shoulders is a common skeletal find. The aim of this study is to report two clinical cases of CCD in two female patients, in which the dentist’s knowledge about the clinical and radiographic aspects characteristic of the disease allowed the correct diagnosis of the condition.